Changes of Morpho-physiological Traits, Essential Oil and Methyl Chavicol Content of Tarragon (Artemisia dracunculus) to Mycorrhiza (Glomus intraradices) Inoculation and Salinity Stress - A Lamian; A Ladan Moghadam; A Ladan Moghadam; A Mehrafarin (Institue of Medicinal Plants, ACECR, 2015)
Background: Tarragon (Artemisia dracunculus L.) from compositae family is important in the medicinal and nutritional industries and traditional medicine. Mycorrhiza fungi (Glomus intraradices) as an important biological fertilizer and synergist with plants can improve the plants resistance to environmental stresses. Objective: The objectives were to evaluate the interaction effects of mycorrhiza (Glomus intraradices) inoculation and salinity stress on morpho-physiological characteristics and essential oil content of tarragon (Artemisia dracunculus L.). Methods: This factorial experiment was conducted at research greenhouse of Medicinal Plants Institute (MPI) on the basis of randomized complete blocks design with 10 treatments and 3 replications. First factor was in two levels of inoculation and non-inoculation of mycorrhiza fungi, and second factor was five levels of salinity (control, 2, 4, 6, and 8 dS.m-1). Results: The analysis of variance showed that interaction effects of fungi inoculation and salt stress was significant on the studied parameters except for stem diameter and root length. The results showed that the most essential oil content (1.15%) was observed in the treatment of mycorrhiza fungi non-inoculation and salinity control and the most methyl chavicol content was attained in the inoculated plants by mycorrhiza fungi, and control treatment. Conclusion: In general, treatment of inoculation and control, and also treatment of fungi non-inoculation and control positively improved the dry weight of plant aerial parts and the essential oil content, respectively.